THE CORRELATIONS BETWEEN EMOTIONAL INTELLIGENCE AND SPIRITUAL INTELLIGENCE TO AGGRESSIVE BEHAVIOR IN HIGH SCHOOL STUDENTS OF SMAN 6 BANDA ACEH - Lisdayani, Lisdayani; Lubis, Lahmuddin; Azis, Azhar (Psikoislamedia: Jurnal Psikologi, 2021)
This research aims to determine the relationship of emotional intelligence and spiritual intelligence with aggressive behavior in SMA Negeri 6 Banda Aceh. The subjects in this research were student of SMA 6 Banda Aceh as many as 40 people. The sampling technique in this research is using purposive sampling technique. The measuring instruments that used in this study are the scale of emotional intelligence, the scale of spiritual intelligence and the scale of aggressive behavior. Based on the results of the analysis using the statistical method of multiple linear regression analysis showed that from the two independent variables of emotional intelligence and spiritual intelligence with the dependent variable is the aggressive behavior has a significant negative relationship, as shown by (R = -0.645;  = 0.416; F = 13.183; p = 0.000). These two independent variables have effective contribution of 41.6% against the aggressive behavior. The other results in this research note that the variables of the emotional intelligence has been associated with aggressive behavior with effective contribution of 15.5% while the spiritual intelligence variables has been associated with aggressive behavior with the effective contribution of 40.9%.